1s2p RIXS Calculations for 3d Transition Metal Ions in Octahedral Symmetry - Patric Zimmermann; Myrtille O. J. Y. Hunault; Frank M. F. de Groot (Journal of Spectroscopy)
We present a series of 1s2p resonant inelastic X-ray scattering (RIXS) calculations for 3d transition metal ions in octahedral symmetry covering each ground state between 3d0 and 3d9. The calculations are performed in octahedral (Oh) symmetry using the crystal field multiplet theory. We discuss the crystal field effects and the selection rules with respect to the 1s2p RIXS pre-edge and compare their final state energies with the corresponding 2p X-ray absorption spectrum (XAS). The calculations provide a detailed understanding of 1s2p RIXS and serve as a basis for the future analysis of experimental spectra and also as a starting point for calculations that add additional channels including the nonlocal peaks.